Process evaluation of the SHARE intervention for preventing intimate partner violence and HIV infection in Rakai, Uganda - Wagman, Jennifer A.; Gray, Ronald H.; Nakyanjo, Neema; McClendond, Katherine A.; Bonneviea, Erika; Namatovu, Fredinah; Kigozi, Grace; Kagaayi, Joseph; Wawer, Maria J.; Nalugoda, Fred (Evaluation and program planning, 2018)
The Safe Homes And Respect for Everyone (SHARE) intervention introduced an intimate partner violence (IPV) prevention approach into Rakai Health Sciences Program, an established HIV research and service organization in Uganda. A trial found exposure to SHARE was associated with reductions in IPV and HIV incidence. This mixed methods process evaluation was conducted between August 2007 and December 2009, with people living in SHARE intervention clusters, to assess awareness about/participation in SHARE, motivators and barriers to involvement, and perceptions of how SHARE contributed to behavior change. Surveys were conducted with 1407 Rakai Community Cohort Study participants. Qualitative interviews were conducted with 20 key informants. Most (77%) were aware of SHARE, among whom 73% participated in intervention activities. Two-thirds of those who participated in SHARE felt it influenced behavior change related to IPV. While some felt confident to take part in new IPV-focused activities of a well-established program, others were suspicious of SHARE’s motivations, implying awareness raising is critical. Many activities appealed to the majority (e.g., community drama) while interest in some activities was limited to men (e.g., film shows), suggesting multiple intervention components is ideal for wide-reaching programming. The SHARE model offers a promising, acceptable approach for integrating IPV prevention into HIV and other established health programs in sub-Saharan Africa.
Keywords: Process evaluation;SHARE intervention; Intimate partner violence; HIV infection; Mixed methods; Rakai Uganda